Triazine-Based Two-Dimensional Organic Polymer for Selective NO2 Sensing with Excellent Performance - Yang, Kai; Yuan, Wenjing; Hua, Zhongqiu; Tang, Yanting; Yin, Fuxing; Xia, Dan (ACS applied materials & interfaces, 2020)
Gas sensors with high sensitivity, fast response/recovery, good selectivity, and room-temperature operation are highly desirable for practical use. However, most of the existing gas sensing materials, either conventional metal oxide semiconductors or advanced inorganic two-dimensional (2D) polymers, can hardly satisfy the above requirements. Herein, we demonstrate an organic 2D polymer derived from a covalent triazine framework (CTF), which possesses nanoscale thickness, intrinsic and periodic pore structures, and abundant functional groups with excellent gas sensing performance. The as-prepared triazine-based 2D polymer (T-2DP) exhibits selective recognition to NO2 with an ultrahigh sensitivity of 452.6 ppm-1, which outperforms most other 2D nanomaterials and its CTF matrix. The sensing effect is superfast (35-47 s) and fully reversible operated at room temperature. The superior comprehensive gas sensing performance of T-2DP and the underlying mechanism was experimentally studied and further discussed by comparison with that of CTF and widely investigated inorganic 2D polymers including graphene and MXene. As a proof of concept, a flexible NO2 chemiresistor based on T-2DP was fabricated to demonstrate its potential for integration into wearable electronics. The scientific findings in this work may propose a new route for the design of high-performance gas sensing materials on the basis of organic 2D polymers in next-generation wearable electronic devices.Gas sensors with high sensitivity, fast response/recovery, good selectivity, and room-temperature operation are highly desirable for practical use. However, most of the existing gas sensing materials, either conventional metal oxide semiconductors or advanced inorganic two-dimensional (2D) polymers, can hardly satisfy the above requirements. Herein, we demonstrate an organic 2D polymer derived from a covalent triazine framework (CTF), which possesses nanoscale thickness, intrinsic and periodic pore structures, and abundant functional groups with excellent gas sensing performance. The as-prepared triazine-based 2D polymer (T-2DP) exhibits selective recognition to NO2 with an ultrahigh sensitivity of 452.6 ppm-1, which outperforms most other 2D nanomaterials and its CTF matrix. The sensing effect is superfast (35-47 s) and fully reversible operated at room temperature. The superior comprehensive gas sensing performance of T-2DP and the underlying mechanism was experimentally studied and further discussed by comparison with that of CTF and widely investigated inorganic 2D polymers including graphene and MXene. As a proof of concept, a flexible NO2 chemiresistor based on T-2DP was fabricated to demonstrate its potential for integration into wearable electronics. The scientific findings in this work may propose a new route for the design of high-performance gas sensing materials on the basis of organic 2D polymers in next-generation wearable electronic devices.